Aponogeton kannangarae, a new species of Aponogeton (Aponogetonaceae) from Rakwana hills, Sri Lanka - Silva, Madura Anusha De; Deshaprema, K. M. S.; Manamperi, J. P. J. (Phytotaxa, 2016)
Aponogeton kannangarae, a new species of Aponogetonaceae from Rakwana hills, Sri Lanka, is described and illustrated. The new species is morphologically similar to A. rigidifolius, but the former can be easily distinguished by morphological characters of its plumule, inflorescence, flowers and rhizome. A key to all Aponogeton species in Sri Lanka is also presented.